BEST PRACTICES IN MBKM CURRICULUM IMPLEMENTATION AT STATE UNIVERSITIES IN INDONESIA - Kusumaningrum, Hesti; Munawwaroh, Zahrotul; Lolytasari, Lolytasari; Azahra, Salsabila (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
The Freedom of Learning–Independent Campus (MBKM) policy serves as a key strategy for higher education reform in Indonesia. This study explores the implementation of the MBKM curriculum in the Educational Management Study Program at Universitas Negeri Jakarta and Universitas Negeri Malang using a qualitative approach. The findings indicate that internship programs, social projects, and teaching assistance enhance students’ competencies and the relevance of learning to labor market demands. However, challenges remain in terms of coordination, lecturers’ digital readiness, differences in academic culture. Therefore, strengthening the role of lecturers, expanding external partnerships, developing an adaptive curriculum are required to ensure the sustainability of MBKM implementation and improve the quality of higher education in Indonesia